2005
DOI: 10.1016/j.molcel.2004.11.047
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Ligand Binding Suppressor Domain of Type 1 Inositol 1,4,5-Trisphosphate Receptor

Abstract: Binding of inositol 1,4,5-trisphosphate (IP(3)) to the amino-terminal region of IP(3) receptor promotes Ca(2+) release from the endoplasmic reticulum. Within the amino terminus, the first 220 residues directly preceding the IP(3) binding core domain play a key role in IP(3) binding suppression and regulatory protein interaction. Here we present a crystal structure of the suppressor domain of the mouse type 1 IP(3) receptor at 1.8 A. Displaying a shape akin to a hammer, the suppressor region contains a Head sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
161
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(182 citation statements)
references
References 54 publications
21
161
0
Order By: Relevance
“…Because of the absence of a high-resolution structure for any domain in RyR1, we used comparative modeling to further interpret the structure. Using sequence and structural analysis (16)(17)(18), a structural homolog was identified with high confidence for two segments at the RyR1 N terminus: the ligand-binding suppressor domain [Protein Data Bank (PDB) ID code 1XZZ (19)] for residues Q12-S207 and the IP 3 -binding core region [PDB ID code 1N4K (20)] of the type 1 inositol 1,4,5-trisphosphate receptor (IP 3 R1) for residues G216-Y565 (Fig. 3A and Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the absence of a high-resolution structure for any domain in RyR1, we used comparative modeling to further interpret the structure. Using sequence and structural analysis (16)(17)(18), a structural homolog was identified with high confidence for two segments at the RyR1 N terminus: the ligand-binding suppressor domain [Protein Data Bank (PDB) ID code 1XZZ (19)] for residues Q12-S207 and the IP 3 -binding core region [PDB ID code 1N4K (20)] of the type 1 inositol 1,4,5-trisphosphate receptor (IP 3 R1) for residues G216-Y565 (Fig. 3A and Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Additional support came from the threading program mGenThreader (16), which identified the same two homologs with very high confidence (P values are 2e-05 and 9e-07). Residues Q12-S207 share a fold with the ligand binding suppressor domain (PDB ID code 1XZZ, sequence identity 19%) (19). Residues G216 -Y565 share a fold with the IP 3-binding core of the IP3R1 channel (PDB ID code 1N4K, sequence identity 16%) (Figs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The question that arises is how disassembly of the complexes occurs under physiological conditions and its role in regulating TRPC3 activity. A clue was provided by a recent crystal structure of the ligand-binding suppressor domain of the IP 3 R1, which showed that the Homer binding motif of the IP 3 Rs is adjacent to the IP 3 binding core (43). We reasoned that binding of IP 3 to activate the IP 3 Rs and evoke Ca 2Ï© release from the stores may also allosterically inhibit binding of H1 to the IP 3 Rs and dissociate the TRPC3-H1b/c-IP 3 Rs complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, and despite their rather low sequence identities ( 30%), the crystal structures of the SD from IP 3 R1 (Bosanac et al 2005) and of the analogous N-terminal regions from RyR1 and RyR2 (Amador et al 2009;Lobo and Van Petegem 2009) are extremely similar. Several mutations associated with malignant hyperthermia and central core disease (RyR1) or catecholaminergic polymorphic ventricular tachycardia (RyR2), all of which impair the normal regulation of gating, are clustered in an exposed loop (b8-b9) of the N-terminal of RyR (Amador et al 2009).…”
Section: Structural Determinants Of Ip 3 R Activationmentioning
confidence: 96%